Musical Metaverse: vision, opportunities, and challenges - Turchet, Luca (Personal and ubiquitous computing, 2023)
The so-called metaverse relates to a vision of a virtual, digital world which is parallel to the real, physical world, where each user owns and interact through his/her own avatar. Music is one of the possible activities that can be conducted in such a space. The “Musical Metaverse” (MM), the metaverse part which is dedicated to musical activities, is currently in its infancy, although is a concept that is constantly evolving and is progressing at a steady pace. However, to the best of the author’s knowledge, as of today an investigation about the opportunities and challenges posed by the MM has not been conducted yet. In this paper, we provide a vision for the MM and discuss what are the opportunities for musical stakeholders offered by current implementations of the MM, as well as we envision those that are likely to occur as the metaverse emerges. We also identify the technical, artistic, ethical, sustainability, and regulatory issues that need to be addressed so for the MM to be created and utilized in efficient, creative, and responsible ways. Given the importance and timeliness of the MM, we believe that a discussion on the related opportunities and concerns is useful to provide developers with guidelines for creating better virtual environments and musical interactions between stakeholders.